PENGELOLAAN TANAH WAKAF SEBAGAI SARANA PEMBERDAYAAN MASYARAKAT - Musthofa, Musthofa (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2019)
Legal development aims to establish and secure the implementation of development and its results. The effort that needs to be done to achieve that goal is by reforming the law in a directed and integrated manner and supporting development in various fields as well as legal awareness and dynamics that develop in the ummah. One of the efforts towards the development of law, among others relating to; First, Land, which has been regulated in PP. No. 28/1977 concerning the representation of property as the implementing regulation of article 49 paragraph 3 of the Law. No 5/1960 Basic Principles of Agrarian Affairs. Second, the law (Islamic jurisprudence). Land "waqf", In law (fiqh) Islamic waqf is worth shadaqah jariah or practice whose reward always flows even though the person who has done so has died, as long as the waqf property is still effective. Waqf is a religious facility that closely related to efforts to achieve prosperity and as a means of empowering people. Waqf practices are very significant for socio-economic, cultural and religious life. Therefore, Islam puts the practice of waqf as one of the practices of worship in which the person who works it will be given joy by Allah.